The Influence of Board Characteristics on ESG Performance - Sihombing, Sergyo Reziro (JURNAL AKUNTANSI DAN AUDITING, 2025)
This study aims to examine the influence of board characteristic which are board tenure, board remuneration, woman on board, and board age on ESG performance in companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this study are all companies listed on the Indonesia Stock Exchange from 2019-2022, companies that make or complete annual reports and sustainability reports from 2019-2022, and companies that have ESG scores available during the observation period from 2019-2022. The sampling technique in this study used purposive sampling technique and obtained a sample of 28 companies. The data analysis method used is multiple regression analysis. The results of this study indicate that board tenure negatively influences the ESG performance, woman on board influences the ESG performance, board educational background and board age does not influence the ESG performance. Keywords: ESG Performance, Board Tenure, Board Remuneration, Woman on Board, Board Age